The domestication of short videos: Experiences of the elderly users from Nanjing, China - Wang, Yinghe; Samani, Mus Chairil; Ahmad, Abdul Latiff (Edelweiss Applied Science and Technology, 2025)
This study explores the domestication of short videos among elderly users in Nanjing based on domestication theory to enable an understanding of the appropriation, objectification, integration, and conversion of these technologies into their everyday lives. Employing qualitative research, the study involved administering semi-structured interviews to 15 participants who are at least 60 years of age. The study is concerned with the factors influencing elderly people’s usage of short video platforms, the difficulties they encounter, and the roles that short video platforms play in their social relations, schedules, and self-presentation. According to the research findings, the initial adoption of short video platforms is first initiated by family members or due to the novelty factor, while long-term usage by the elderly is often a part of recreation, communication, and education. In this sense, participants expressed the benefits of short videos, including social integration and the connection between generations, despite technical restrictions and content-related issues. This study provides a range of methodical recommendations for platform creators and regulatory bodies to improve elderly users’ digital engagement and integration.